2016
DOI: 10.1111/jog.13186
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D restores angiogenic balance and decreases tumor necrosis factor‐α in a rat model of pre‐eclampsia

Abstract: Vitamin D supplementation plays an important role in restoring angiogenic balance and reducing inflammation in pregnancy-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
(83 reference statements)
2
17
0
Order By: Relevance
“…Although sFlt‐1 is commonly increased in preeclampsia and experimental hypertension‐in‐pregnancy, no differences were observed in sFlt‐1 plasmatic levels in HTN‐Preg animals, as previously reported in different animal models of hypertension‐in‐pregnancy . Also, glucocorticoids, such as desoxycorticosterone acetate may present anti‐inflammatory effects and since reductions in inflammation have been related to decreases in sFlt‐1, such effect of desoxycorticosterone acetate may have blunted increases in sFlt‐1 in our hypertensive pregnant animals. Moreover, PlGF plasmatic levels were diminished in Preg+NaHS, HTN‐Preg and HTN‐Preg+NaHS groups.…”
Section: Discussionsupporting
confidence: 73%
“…Although sFlt‐1 is commonly increased in preeclampsia and experimental hypertension‐in‐pregnancy, no differences were observed in sFlt‐1 plasmatic levels in HTN‐Preg animals, as previously reported in different animal models of hypertension‐in‐pregnancy . Also, glucocorticoids, such as desoxycorticosterone acetate may present anti‐inflammatory effects and since reductions in inflammation have been related to decreases in sFlt‐1, such effect of desoxycorticosterone acetate may have blunted increases in sFlt‐1 in our hypertensive pregnant animals. Moreover, PlGF plasmatic levels were diminished in Preg+NaHS, HTN‐Preg and HTN‐Preg+NaHS groups.…”
Section: Discussionsupporting
confidence: 73%
“…38 Similarly, the role of vitamin D in restoring angiogenic balance by increasing VEGF levels has also been demonstrated in a pregnancy-induced hypertension rat model. 39 In our study, the size of the official cavities and the number of official cavity-like structures formed by MSCs treated with 1,25(OH) 2 D 3 were significantly increased. After blocking the VDR channel with pyridoxal-5-phosphate, the cell-to-tube capacity of MSCs was significantly weakened, demonstrating that 1,25(OH) 2 D 3 promotes vasculogenesis of MSCs, which is mediated by the VDR.…”
Section: Discussionsupporting
confidence: 50%
“…In their post-hoc analysis derived from the VDAART RCT, Mirzakhani et al ( 17 ) reported that a key factor in preventing preeclampsia was vitamin D status early in pregnancy: first trimester circulating 25(OH)D concentration of a least 100 nmol/L (40 ng/mL) was associated with a reduction in the risk of developing preeclampsia. Predicted by both observational studies as well as experimental animal models, the association of vitamin D deficiency and its ability to alter placental development and embryo implantation is further supported by the findings of Mirzakhani et al ( 15 , 17 , 103 , 104 ). As mentioned earlier, this effect is likely vitamin D-mediated during a very early point in pregnancy.…”
Section: Vitamin D-induced Genomic Alterations During Pregnancymentioning
confidence: 72%